Activity-associated miRNA are packaged in Map1b-enriched exosomes released from depolarized neurons. Issue 14 (22nd July 2014) - Goldie, Belinda J.; Dun, Matthew D.; Lin, Minjie; Smith, Nathan D.; Verrills, Nicole M.; Dayas, Christopher V.; Cairns, Murray J.
Abstract: Rapid input-restricted change in gene expression is an important aspect of synaptic plasticity requiring complex mechanisms of post-transcriptional mRNA trafficking and regulation. Small non-coding miRNA are uniquely poised to support these functions by providing a nucleic-acid-based specificity component for universal-sequence-dependent RNA binding complexes. We investigated the subcellular distribution of these molecules in resting and potassium chloride depolarized human neuroblasts, and found both selective enrichment and depletion in neurites. Depolarization was associated with a neurite-restricted decrease in miRNA expression; a subset of these molecules was recovered from the depolarization medium in nuclease resistant extracellular exosomes. These vesicles were enriched with primate specific miRNA and the synaptic-plasticity-associated protein MAP1b. These findings further support a role for miRNA as neural plasticity regulators, as they are compartmentalized in neurons and undergo activity-associated redistribution or release into the extracellular matrix.